Climate visuals: A mixed methods investigation of public perceptions of climate images in three countries. (November 2016) - Chapman, Daniel A.; Corner, Adam; Webster, Robin; Markowitz, Ezra M.
Highlights: Little extant climate change communication research examines the impact of imagery. Perceived authenticity and credibility importantly influenced image evaluations. Familiar climate images were easily understood but also attracted cynicism. Images of 'solutions' produced positive affective responses and less polarization. Images of 'impacts' produced greater intentions towards personal behavioral change. Abstract: Imagery plays a central role in climate change communication. But whereas research on the verbal communication of climate change has proliferated, far fewer studies have focused on visual communication. Correspondingly, relatively little is known about how to effectively engage the public using the visual medium. The current research is the first mixed methods, cross-national investigation of public perceptions of climate images, with a focus on photographic climate change imagery. Four structured discussion groups in the UK and Germany ( N = 32) and an international survey with an embedded experiment in the UK, Germany and the US ( N = 3014) were conducted to examine how different types of climate change imagery were evaluated. The qualitative research pointed to the importance of the perceived authenticity and credibility of the human subjects in climate images, as well as widespread negativity towards images depicting protests and demonstrations. Images of climate 'solutions' produced positive emotional responses in the survey and were less polarizing for climate change skeptics, but they were also the least motivating of action. Familiar climate images (such as a polar bear on melting ice) were easily understood in the survey (and evaluated positively as a consequence) but viewed with cynicism in discussion groups. We present a detailed discussion of these and other key findings in this paper and describe a novel application of the data through an online image library for practitioners which accompanies the research (www.climatevisuals.org ).